On Invariant Approximations in Modular Spaces - Mohammed, Nadia Jasim; Abed, Salwa Salman (Iraqi Journal of Science, 2021)
This article is devoted to presenting results on invariant approximations over a non-star-shsped weakly compact subset of a complete modular space by introduced a new notion called S-star-shaped with center f: if be a mapping and , . Then the existence of common invariant best approximation is proved for Banach operator pair of mappings by combined the hypotheses with Opial’s condition or demi-closeness condition